Potential and Challenges of Digital Governance at the Local Level in Central Sulawesi, Indonesia - Kisman Karinda; Erwin Nursin; Muhammad Sawir; Thanaporn Sriyakul (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2024)
Many countries, as well as several regions in Indonesia, are adopting digital government with the urgency that this approach is helpful as a bridge to good governance. However, more examination is needed to see both the opportunities and obstacles of digital government by assessing cases at the local level. This research analyses the potential and challenges of developing digital government locally with a case study in Central Sulawesi Province. The region was selected for analysis because Central Sulawesi has developed the necessary telecommunications infrastructure and internet access. The study relies on online research methods to collect data and information via the internet and other digital technology. This study employs NVivo 12 Plus for analysis. The findings of this research reveal that Central Sulawesi has great potential in developing digital government, such as optimising data management, accelerating administrative processes and increasing citizen involvement. However, the study also identifies challenges, such as poor access to digital infrastructure in rural areas and limited digital skills among government employees. Therefore, strong efforts are needed to expand the reach of internet access, improve digital skills and increase citizen participation in the development of digital government. This research provides an in-depth understanding of the potential and challenges of developing digital government in Central Sulawesi as well as relevant policy recommendations to increase digital adaptation at the local level.